Claudins and pathogenesis of viral infection. (June 2015) - Tawar, Rajiv G.; Colpitts, Che C.; Lupberger, Joachim; El-Saghire, Hussein; Zeisel, Mirjam B.; Baumert, Thomas F.
Abstract: Since their discovery, tremendous progress has been made in our understanding of the roles of claudins in tight junction physiology. In addition, interactions between claudins and other cellular proteins have highlighted their novel roles in cell physiology. Moreover, the importance of claudins is becoming apparent in the pathophysiology of several diseases, including viral infections. Notable is the discovery of CLDN1 as an essential host factor for hepatitis C virus (HCV) entry, which led to detailed characterization of CLDN1 and its association with tetraspanin CD81 for the initiation of HCV infection. CLDN1 has also been shown to facilitate dengue virus entry. Furthermore, owing to the roles of claudins in forming anatomical barriers, several viruses have been shown to alter claudin expression at the tight junction. This review summarizes the role of claudins in viral infection, with particular emphasis on HCV.